Analysis of the Leading Economic Sectors of the City of Sibolga - Sirait, Ruth Oktavia; Naukoko, Amran T.; Rompas, Wensy F. I (PT FORMOSA CENDEKIA GLOBAL, 2024)
National development includes economic growth. Economic development was initially focused on regional expansion. The basic sectors in Sibolga City that could grow into top sectors are looked at in this study. To help Sibolga City's economy grow faster from 2012 to 2023, this study tries to find the most important and growing economic areas. This study uses quantitative descriptive methods. The literature review strategy employed in this study involves reading books and articles from relevant scientific journals. The study used North Sumatra Province and Sibolga City Central Statistics Agency (BPS) data. The Location Quatient analysis model (LQ), Dynamic Location Quatient (DLQ), and Shift Share will then manage it. Three businesses were named outstanding by the survey. Examples include the following: wholesale and retail trade, transportation and storage, lodging, food and drink service, and the repair of motor vehicles and motorcycles.